The Capture Process in the Crime of Murder by A Special Team - Eka Rinda Wanto; Rakhmat Bowo Suharto; Siti Rodhiyah Dwi Istinah (Universitas Islam Sultan Agung, 2022)
The aims of this paper are as follows: To find out and analyze the process of arrest in the crime of murder by a special team. To find out and analyze the obstacles and solutions in the arrest process in the crime of murder by a special team. This study uses a sociological juridical approach, with descriptive analysis research specifications. The data used in this study is secondary data obtained through literature study which is then analyzed qualitatively. The results of this study are the process of arresting in the crime of murder by a special team is: Arresting the perpetrator if the perpetrator is still within the reach of investigators to be arrested immediately. Closing the scene of the incident to anyone whose presence there is not required to save the victim, to save people's assets or for the purposes of investigation and investigation with the intention that the place of the incident of the case remains in its original state to facilitate the process of investigation and investigation. Finding, rescuing, collecting, and retrieving evidence and traces that can help investigators to obtain clues about the identity of the perpetrator, about the methods and tools used to commit the crime, as well as to determine where the crime scene occurred. Finding witnesses who are expected to help investigators to solve problems in the crime incident. The obstacle: Changes in the authenticity of the place that occurred at the scene of the case. Lack of experience of investigators in conducting investigations. The absence of completeness of equipment at the time of investigations. Investigators' efforts in overcoming the lack of completeness of tools to conduct investigations. Investigators' efforts to overcome the unavailability of a database on fingerprinting.